Contract Law and Default in Indonesian E-Commerce Transactions: Legal Certainty, Consumer Protection, and the Future of Digital Contract Enforcement - David Nwanna Dumbiri; Luluk Makhmia; Putri Wulan Mandasari; Yoga Dwi Firmansyah; Firza Agung Prakos (ISNU Sumatera Utara, 2026)
The rapid expansion of electronic commerce has fundamentally transformed contractual relationships by enabling legally binding transactions to be concluded through digital platforms without physical interaction between contracting parties. While this transformation has improved commercial efficiency, it has simultaneously generated increasingly complex legal issues concerning contractual validity, breach of contract, consumer protection, and dispute resolution. In Indonesia, although online agreements are recognized under the Civil Code and electronic transaction regulations, cases of default in e-commerce transactions continue to demonstrate a significant gap between normative legal provisions and practical enforcement. This study aims to analyze the implementation of Indonesian contract law in online purchase transactions, examine the legal consequences of default committed by sellers, and evaluate the effectiveness of existing legal mechanisms in providing legal certainty and consumer protection within the digital economy. The research employs a normative juridical method using statutory, conceptual, comparative, and case approaches. Legal materials were collected from primary legislation, legal doctrines, judicial opinions, and international legal instruments, and were analyzed through qualitative legal reasoning supported by systematic and comparative legal interpretation. The findings indicate that electronic contracts possess the same binding legal force as conventional agreements provided that the requirements stipulated in Article 1320 of the Indonesian Civil Code are fulfilled. Nevertheless, legal enforcement remains constrained by weak contractual compliance, unequal bargaining positions between consumers and business actors, fragmented dispute resolution mechanisms, and limited integration between conventional contract law and digital commerce regulations. This study proposes an Integrated Digital Contract Enforcement Model that combines civil law principles, electronic transaction regulation, consumer protection mechanisms, and online dispute resolution to strengthen legal certainty and enhance contractual justice within Indonesia's evolving digital economy.